Flavor physics in the Randall-Sundrum model: II. Tree-level weak-interaction processes - Bauer, Martin (Journal of high energy physics, 2010)
A comprehensive analysis of tree-level weak interaction processes at low energy is presented for the Randall-Sundrum (RS) model with SU(2)L × U(1)Y bulk gauge symmetry and brane-localized Higgs sector. The complete form of the effective weak Hamiltonian is obtained, which results from tree-level exchange of Kaluza-Klein (KK) gluons and photons, the W± and Z0 bosons and their KK excitations, as well as the Higgs boson. Exact expressions are used for the bulk profiles of the various fields, and for the exchange of entire towers of KK gauge-boson states. A detailed phenomenological analysis is performed for potential new-physics effects in neutral-meson mixing and in rare decays of kaons and B mesons, including both inclusive and exclusive processes. We find that while the predictions for ∆F = 2 observables are rather model-independent, ∆F = 1 processes depend sensitively on the exact realizations of the electroweak gauge and the fermionic sector. In this context, we emphasize that the localization of the right-handed top quark in the extra dimension plays a crucial role in the case of rare Z0-mediated decays, as it determines the relative size of left- to right-handed couplings. We also extend earlier studies of quark flavor-changing neutral currents by examining observables which up to now attracted little attention. These include D−D¯¯¯¯D−D¯ D - \overline D mixing, B → τντ, B → Xs(K*) l+l-, ϵ′K/ϵK, B¯¯¯¯→πK¯¯¯¯¯B¯→πK¯ \overline B → π \overline K , B¯¯¯¯0→ϕKSB¯0→ϕKS {\overline B^0} → φ {K_S} , B¯¯¯¯0→η′KSB¯0→η′KS {\overline B^0} → η '{K_S} , and B+ → π+π0.
Gesehen am 21.11.2017